Mataroa 1945 : du mythe à l'histoire - Jollivet, Servanne; Manitakis, Nicolas (Mondes méditerranéens et balkaniques (MMB), 2020)
The Mataroa, a military vessel chartered by the French Institute at Athens in December 1945, enabled more than a hundred young Greeks to leave Greece, reaching first Taranto, Italy, and finally arriving in Paris. Leaving a country that was in ruins, deeply weakened by war and on the verge of civil war, they were thus welcomed in France, to pursue their studies and careers in fields as varied as philosophy, sculpture, architecture, music, etc. At the heart of this expedition was the director of the French Institute at Athens at that time, Octave Merlier, who made this operation, which looks like a modern epic, possible. Long overlooked, this trip is undoubtedly one of the most significant events in post-war Franco-Greek history. Based on unpublished archival material, this volume aims to shed historical and critical light on this event, sometimes obliterated, sometimes mythologized, but an integral part of the memory of the exchanges between the two countries.